Effects of laminarin on antioxidant capacity and non-specific immunity of spotted sea bass (Lateolabrax maculatus) - Sishun Zhou; Huihui Qin; Zhongying Long; Lumin Kong; Jianrong Ma; Yi Lin; Hao Lin; Zhangfan Huang; Zhongbao Li (Aquaculture Reports)
As a prebiotic, laminarin has functions such as antioxidant and improving the body's immunity. This study explores the antioxidant capacity and nonspecific immune effects of laminarin by adding different concentration gradients (0 %, 0.4 %, 0.8 %, 1.2 %, 1.6 %, and 2 %) to the diet of spotted sea bass, Lateolabrax maculatus. 450 spotted sea bass (initial weight: 7.14 ± 0.10 g) were randomly divided into 6 groups, each group was repeated 3 times, 25 fish per experimental tank, and fed with different concentrations of laminarin. After 56 days of feeding, samples were collected and measured for antioxidant capacity and non-specific immune indicators. The results show that, in terms of antioxidant capacity, the dietary addition of 0.8 % laminarin significantly increased the serum total antioxidant capacity, glutathione content, and superoxide dismutase activity in spotted sea bass (P < 0.05). In addition, 0.4–0.8 % laminarin supplementation significantly increased the total antioxidant capacity and catalase activity and decreased the malondialdehyde content in the spleen of the spotted sea bass (P < 0.05). Dietary addition of 0.8–1.2 % laminarin significantly increased glutathione content in head kidney (P < 0.05). In terms of immunity, the addition of 0.8 % laminarin to the diet significantly increased serum acid phosphatase, serum lysozyme, spleen lysozyme, and head kidney acid phosphatase activities in spotted sea bass (P < 0.05). The addition of 0.4–0.8 % laminarin to the diet significantly increased serum immunoglobulin M, head kidney lysozyme activity (P < 0.05). Diet supplemented with 0.8 % laminarin induced 739 differential genes in head kidney. The differentially expressed genes in head kidney were significantly enriched in immune-related pathways. In conclusion, dietary 0.8 % laminarin supplementation can promote the antioxidant capacity and non-specific immunity of juvenile spotted sea bass.